A study on the relationship between teamwork and employees' job performance at Menara Telekom Malaysia, Kuala Lumpur / Syaieznor Aznieza Ahmad Rosli - Ahmad Rosli, Syaieznor Aznieza (2016)
This study was conducted to study on relationship between teamwork and employees' job performance at Menara Telekom Malaysia Berhad (TM), Kuala Lumpur. Another objective of this study was to identify the factor of teamwork that will affects on employee's job performance at Menara TM. There were three dimension of teamwork had been selected in which team trust, interdependence, and reward and recognition. The type of research is correlational research and the questionnaire was used for data collection. The measuring instrument used was simple random sampling which is 80 questionnaires had been returned. The study was limited to the employees' who were working at the headquarters of Telekom Malaysia Berhad. Data was analyzed by using Statistical Package for Social Science (SPSS) for Windows version 21.0 to get the statistical for the questionnaires. Descriptive statistic was used to measure the level of teamwork on employees' job performance. The most influential factor of teamwork that affect to employees' job performance was interdependence. Pearson correlation coefficient statistic was used to identify the relationship between teamwork towards the employees' job performance. Based on the result, there was a relationship between all dimension of teamwork and employees' job performance at Menara TM.